ORIENTASI ENTREPRENEURIAL SOSIAL ANALISIS STATE OF THE ART BERDASARKAN SYNTHETIC SCOPING REVIEW - Ivan Yulivan; Nur Dina; Iwan Sukoco; Margo Purnomo; Dian Fordian (AdBispreneur : Jurnal Pemikiran dan Penelitian Administrasi Bisnis dan Kewirausahaan, 2021)
The purpose of the research using the synthetic scoping review method is to reveal state-of-the-art of entrepreneurial orientation study in social entrepreneurship context. This research was carried out in a mixed method approach with three stages, namely systematic review and scoping review as a qualitative approach and bibliometric mapping with co-occurrence analysis as a quantitative approach. The results of a systematic review show that a social entrepreneurial orientation has been initiated since 2002.. The European Union and quantitative research dominate. The results of the scoping review reveal seven dimensions of entrepreneurial orientation that are typical with social entrepreneurship context. Furthermore, the results of the co-occurrence analysis raise five major themes, namely 1) the effect of social entrepreneurial orientation on entrepreneurial financial performance, 2) economic performance and social performance, 3) Social entrepreneurial orientation in sociopreneurship practice, 4) the antecedent and consequent of the strategic domain of social entrepreneurial orientation and 5) Social entrepreneurial orientation in knowledge spillover theory of entrepreneurship. Based on results, this article contributes to new research opportunities on social entrepreneurial orientation study. Tujuan penelitian dengan metode synthetic scoping review disini adalah mengungkap kondisi terkini (state-of-the-art) kajian orientasi entrepreneurial dalam konteks entrepreneurship sosial. Penelitian dilakukan dengan pendekatan mixed method dalam tiga tahap, yaitu systematic review dan scoping review sebagai pendekatan kualitatif dan bibliometric mapping dengan analisis co-occurrence sebagai pendekatan kuantitatif. Hasil systematic review menunjukkan bahwa orientasi entrepreneurial sosial telah digagas sejak 2002. Uni Eropa dan penelitian kuantitatif mendominasi. Hasil scoping review memunculkan tujuh dimensi orientasi entrepreneurial yang khas dalam konteks entrepreneurship sosial. Selanjutnya, hasil analisis co-occurrence memunculkan lima tema besar, yaitu 1) pengaruh orientasi entrepreneurial sosial terhadap kinerja keuangan entrepreneurial, 2) kinerja ekonomi dan kinerja sosial, 3) orientasi entrepreneurial sosial dalam praktik sociopreneurship, 4) anteseden dan konsekuen domain strategis orientasi entrepreneurial sosial, dan 5) orientasi entrepreneurial social dalam knowledge spillover theory of entrepreneurship. Berdasarkan hasil tersebut, artikel ini berkontribusi membuka peluang penelitian baru dalam kajian orientasi entrepreneurial sosial.